(untitled) (Foro de Educacion, 2026)
Chinese higher education has witnessed accelerated growth, which has raised academic standards but at the same time revealed lingering integrity problems. While studies have demonstrated that teachers’ ethical leadership can influence students’ moral cognition and, ultimately, moral behavior, there is to date limited teacher-focused evidence in a regional context and mostly based on undergraduate students. To test the relationship between teachers’ ethical leadership (TEL) and students’ moral cognition (SMC) and students’ moral behavior (SMB), and to test the mediating effect of SMC on the TEL-SMB relationship. A quantitative cross-sectional survey with deductive and inductive patterns was conducted on undergraduates in six selected stratified-randomly selected universities in Chongqing (N = 407). Validity and reliability of the measurement were determined using CFA/PLS-SEM (Smart PLS 4), then structural modelling using a bootstrapped inference was performed. Cross loadings, composite reliability, and AVE were obtained for all constructs with HTMT < .85. Structural pathways were significant, including TELSMC (O = 0.602, p < .001), SMC-SMB (O = 0.548, p < .001) and a smaller direct TEL-SMB (O = 0.167, p = .004). Complementary mediation was suggested by the significant indirect effect (TEL-SMC-SMB) (O = 0.330, p < .001). R2 was 0.512 (SMC) and 0.476 (SMB). The key to teachers’ ethical leadership positive influence on students’ ethical behaviors was that moral cognition was enhanced by ethical leaders, with a smaller direct behavioral influence. Findings support cognition-to-action mechanisms and provide actionable levers for policy, curriculum, and pedagogy in Chinese universities.